БЎЛАЖАК ИНГЛИЗ ТИЛИ ЎҚИТУВЧИЛАРИДА ГРАММАТИК КОМПЕТЕНЦИЯНИ ШАКЛЛАНТИРИШ БОСҚИЧЛАРИ - Жуманазаров, У.У. (SCIENCE and SOCIETY, 2021)
The article discusses the stages of formation of grammatical competence in pre-service English teachers, the peculiarities of linguistic tasks, cognitive, operational-activity, motivational and reflexive criteria.
Keywords: grammar; competence; linguistics; cognitive; motivation; criterion; degree; linguoculture